Longitudinal profiles of shared book reading in early childhood and children’s academic achievement in Year 3 of school - Hayes, Nicole; Berthelsen, Donna (My University, 2019)
This research examined longitudinal profiles for parental involvement in shared reading with children from age 2 to 6 years. Associations of the profiles with sociodemographics were explored, as well as associations with children’s achievement in Year 3 at school. Data were drawn from Growing Up in Australia: The Longitudinal Study of Australian Children for 3,836 children in the Baby Cohort. Three longitudinal profiles were identified: (1) high-stable involvement, (2) medium-stable involvement, and (3) low-increasing involvement. Profile membership was distinguished by: child Indigenous status and non-English language at home, family socioeconomic position, number of siblings at home, and child’s early self-regulation. Membership in the low-increasing involvement group was associated with the likelihood of not attaining Australian minimum standards for reading, writing, and numeracy. Membership in the medium-stable involvement group was associated with the likelihood of not attaining minimum standards for reading
School Effectiveness and School Improvement
Keywords: Learning, education and training